2004
DOI: 10.1891/088667004780927981
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Trauma Reactions of Bystanders and Victims to Repetitive Abuse Experiences

Abstract: This study investigated psychological distress as measured by the Impact of Events Scale-Revised and physiological reactivity as measured by skin conductance and heart rate in bystanders as compared to direct victims of prevalent forms of repetitive abuse (e.g., bullying). Participants (N = 77) were interviewed twice: once to recall witnessing another person be abused repeatedly over time, and again to recall similar experiences as a victim. Present levels for bystander and victim distress were not significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Student bystanders are present in up to 90% of bullying incidents (Atlas & Pepler, 1998; Craig & Pepler, 1995; Glew et al, 2005; Hawkins, Pepler, & Craig, 2001). Youths who witness bullying often report emotional distress, including increased heart rate and higher levels of fear, sadness, and anger when recalling bullying incidents (Barhight, Hubbard, & Hyde, 2013; Janson & Hazler, 2004). Thus, across the literature, bullying is associated with problematic outcomes for perpetrators, victims, bully–victims, and bystanders alike.…”
Section: Negative Outcomes Connected With Bullyingmentioning
confidence: 99%
“…Student bystanders are present in up to 90% of bullying incidents (Atlas & Pepler, 1998; Craig & Pepler, 1995; Glew et al, 2005; Hawkins, Pepler, & Craig, 2001). Youths who witness bullying often report emotional distress, including increased heart rate and higher levels of fear, sadness, and anger when recalling bullying incidents (Barhight, Hubbard, & Hyde, 2013; Janson & Hazler, 2004). Thus, across the literature, bullying is associated with problematic outcomes for perpetrators, victims, bully–victims, and bystanders alike.…”
Section: Negative Outcomes Connected With Bullyingmentioning
confidence: 99%
“…It has been established that victimization triggers a similar emotional and physical impact both on victims and on bystanders of bullying. In particular, repetitive abuse can affect bystanders and victims when the events occur later in life [ 13 ]. Thus, it can be assumed that bystanders may also consume substances after exposure to bullying.…”
Section: Health and Risk Behaviors Of Bystanders In The Framework Of Cor And Moral Disengagementmentioning
confidence: 99%
“…This line of research has focused on how witnessing bullying acts impacts the well-being and psychological health of bystanders [ 7 ]. It has demonstrated a correlation between witnessing an act of bullying and suicide ideation [ 8 ], symptoms of depression among bystanders [ 9 , 10 , 11 ], especially among those who were exposed to bullying [ 12 ], repression of empathy of bystanders [ 13 ], and increased feelings of guilt [ 4 ]. The underlying assumption of this research approach is that, in the act of bullying, bystanders are passively victimized.…”
Section: Introductionmentioning
confidence: 99%
“….sex life" (Einarsen & Mikkelsen, 2003, p. 132). Research with bullied adults showed lower cortisol levels (Hansen et al, 2006;Janson & Hazler, 2004;Kudielka & Kern, 2004) and reduced tonic activity of the hypothalamic pituitary adrenal (HPA) axis, which is our central stress response system axis (Bellingrath & Kudielka, 2008;Monteleone et al, 2009), with "no statistically significant differences in cortisol levels for social and physical bullying" (Vaillancourt et al, 2008). Some targets are at increased risk for substance abuse, eating disorders, self-destructive behaviours including suicide (Brousse et al, 2008;Hirigoyen, 2001;Leymann, 1996;Matsakis, 1996;Meek, 2004), mood disorders, cardiovascular disease (McEwen, 2000;Xu et al, 2018) and strokes, high blood pressure, abdominal pain, headaches and joint pain (Knack et al, 2014).…”
Section: Physical Symptomsmentioning
confidence: 99%